Melamine phosphate-modified magnetic chitosan: a novel biocompatible catalyst for the synthesis of biological tetrahydrodipyrazolopyridine and pyrazolopyranopyrimidine derivatives - Mousavi-Ebadi, Maryam; Safaei-Ghomi, Javad (Frontiers in Chemistry, 2024)
The functionalization of magnetic chitosan with the melamine phosphate (MP) ionic compound was comprehensively characterized through a range of analytical techniques, including FT-IR, NH3 and CO2-TPD, XRD, TEM, FE-SEM, VSM, EDX, elemental CHNS analysis, ICP-MS, and NMR spectroscopy. Subsequently, the resulting novel biocompatible composite was harnessed to serve as a recoverable and bifunctional catalyst, aiming at the diversity-oriented generation of biological tetrahydropyrazolopyridine and pyrazolopyrimidine derivatives. This involved a meticulously orchestrated reaction, exploiting the in situ generated pyrazole alongside aromatic aldehydes, ammonium acetate, and (thio) barbituric acid. The present work manifests outstanding advantages, offering a novel and great method for the optimal synthesis of two valuable heterocyclic series especially five new derivatives. Notably, the study represents a critical step in the preparation of advanced materials from accessible and cost-effective precursors.